Screening for adverse childhood experiences in antenatal care settings: A scoping review. (31st July 2022) - Tran, Nam; Callaway, Leonie; Shen, Sitong; Biswas, Tuhin; Scott, James G.; Boyle, Fran; Mamun, Abdullah
Abstract : Background: Adverse childhood experiences (ACEs) are associated with many health problems in women during pregnancy, including depression/anxiety, gestational diabetes and adverse birth outcomes. However, unlike other health risk factors, screening for ACEs has not been widely implemented in antenatal care settings. Aims: The aim of the scoping review was to explore the challenges in screening for ACEs in antenatal care settings and to provide the lessons learnt and evidence that guide the practice of ACE screening for both healthcare providers and pregnant women. Methods: A five‐stage process for conducting the scoping review was utilised. Searches of four key databases (PubMed, PsycINFO, CINAHL and SCOPUS) and reference lists from relevant studies were conducted. Results: Seven publications met the inclusion criteria. Challenges identified for healthcare providers in screening for ACEs include lack of knowledge and confidence in ACE tool and shortage of time and resources to undertake screening. Impediments for pregnant women include concerns about privacy. However, there were examples of effective practice for ACE screening in antenatal care settings that could apply widely. Conclusion: Addressing impediments to ACE screening is critical in implementing trauma‐informed practices that can identify women at risk of adverse health outcomes during pregnancy. A study on screening for ACEs in antenatal care in both public and private settings is needed to examine its feasibility and acceptability in the Australian context before being included in the National Perinatal Data Collection.